2009
DOI: 10.1097/scs.0b013e3181843518
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Estimation of the Eyeball Volume Using the Cavalieri Principle on Computed Tomography Images

Abstract: The size of the eyeball has been the subject of a few studies. None of them used stereological methods to estimate the volume. In the current study, we estimated the volume of eyeball in normal men and women using the stereological methods. Eyeball volume (EV) was estimated using the Cavalieri principle as a combination of point-counting and planimetry techniques. We used computed tomography scans taken from 36 participants (15 men and 21 women) to estimate the EV. The mean (SD) EV values obtained by planimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…[3] Consequently, if the volume of one eye is known then the volume of the other eye (if normal) can be extrapolated as it will fall within the calculated value of ±1% of the known eye volume. We reported a total average volume of both eyes of 5282 mm 3 which is smaller than that reported by Galluzzi et al [1] and Acer et al, [9] but less than that reported by de-Graaf et al [10] (mean ocular volume of the normal eyes was put at 6,018 mm 3 , 7,060 mm 3 and 5018 mm 3 respectively). Similarly, in a study in Nesbraska, USA, on CT measured ocular volume on 228 eyeballs, the value obtained was 7,181 mm 3 .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…[3] Consequently, if the volume of one eye is known then the volume of the other eye (if normal) can be extrapolated as it will fall within the calculated value of ±1% of the known eye volume. We reported a total average volume of both eyes of 5282 mm 3 which is smaller than that reported by Galluzzi et al [1] and Acer et al, [9] but less than that reported by de-Graaf et al [10] (mean ocular volume of the normal eyes was put at 6,018 mm 3 , 7,060 mm 3 and 5018 mm 3 respectively). Similarly, in a study in Nesbraska, USA, on CT measured ocular volume on 228 eyeballs, the value obtained was 7,181 mm 3 .…”
Section: Discussioncontrasting
confidence: 66%
“…The difference in ocular volume between the sexes was less than 100 mm 3 which may be considered of minimal significance as it was less than 2%. But this was not the case in the study by Acer et al [9] in which the percentage difference in the mean between ocular volumes of both sexes was about 3.6%. We observed that the patients in our study showed consistent increase in ocular volume in either globe of male patients than of females in those above 60 years.…”
Section: Discussionmentioning
confidence: 68%
“…Because of the lack of a bony anterior border, a manual aid was necessary during the volume determination of the data sets. Nout et al 7 who only used sagittal CT slices, defined the 12,13 The summation of the areas obtained from manual segmentation of a large number of axial or coronal slices could be performed in different ways, including the following: (1) a manual calculation by point-counting and multiplying the surface factors of each element for each slice, (2) a manual outline of each slice and computed calculation, (3) a summation of the cross-sectional areas of each section. [12][13][14][15] Orbital volume measurement with these methods is very time consuming and, therefore, is not clinically useful.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is widely used for ocular biometry in people, both for research and to establish reference ranges for certain cohorts . Standard measurement methods have been established . In veterinary ophthalmology, it would be useful to have breed‐specific reference values for research purposes and for skull CT interpretation.…”
Section: Introductionmentioning
confidence: 99%